"Pay-later" vs. "pay-as-you-go": Experimental evidence on present-biased overconsumption and the importance of timing - Madeline Werthschulte (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2020)
When consuming goods provided by public utilities, such as telecommunication, water, gas or electricity, the predominant payment scheme is pay-later billing. This paper identifies one potential consequence of pay-later schemes, present-biased overconsumption of the respective good, and tests the effectiveness of pay-as-you-go schemes in reducing consumption. Specifically, I run a lab experiment which mimics an energy consumption choice and randomizes the timing of when consumption costs are paid: Either immediately ('pay-as-you-go') or one-week after consumption ('pay-later'). Results show that pay-as-you-go billing significantly decreases consumption, and in particular wasteful consumption. As the design controls for contaminating effects, these results can be solely attributed to present-biased discounting under the pay-later scheme. These results imply that pay-as-you-go schemes will be welfare improving both from agent's own perspective and from a social perspective if externalities are involved. In contrast, classic price-based polices will need correctives to account for present bias arising under pay-later schemes.
Keywords: C91; D15; D91; Q49; 330; payment schemes; present bias; discounting; lab experiment; energy